Women's Political Participation In Kurdistan Region Of Iraq From The Viewpoint Of University Students - Dr Muhammed Saeed Hussain Ahmed (Journal for ReAttach Therapy and Developmental Diversities, 2023)
The aim of the research is to identify the university students' point of view on women's political participation in the Kurdistan Region of Iraq. And the significance of the differences in that according to a number of demographic variables represented by: (social gender, age, housing location). The research relied on the comparative descriptive approach due to its suitability to the nature of the research, and the sample consisted of (140) male and female students who were randomly selected from the students of the Department of Sociology at the University of Duhok. The researcher used a questionnaire prepared for the purpose of the current research, consisting of (25) paragraphs, and in front of each paragraph there are five alternatives for the answer, which are (very agree, agree, neutral, disagree, and do not agree at all). The validity and reliability of the questionnaire were verified. The data contained in the research were processed statistically using means, standard deviations, t-test for one sample and two independent samples, and one-way analysis of variance. The results showed that the level of political participation of women in Iraqi Kurdistan is low from the point of view of university students, and it was found that there is no statistically significant difference in the students' views on women's political participation in Iraqi Kurdistan due to demographic variables: gender, age, and residence location. In light of the results, a set of recommendations and proposals were presented.